2000
DOI: 10.1016/s0014-5793(00)01963-3
|View full text |Cite
|
Sign up to set email alerts
|

Secretional luciferase of the luminous shrimpOplophorus gracilirostris: cDNA cloning of a novel imidazopyrazinone luciferase

Abstract: The deep-sea shrimp Oplophorus gracilirostris secretes a luciferase that catalyzes the oxidation of coelenterazine to emit blue light. The luciferase (M r approx. 106 000) was found to be a complex composed of 35 kDa and 19 kDa proteins, and the cDNAs encoding these two proteins were cloned. The expression of the cDNAs in bacterial and mammalian cells indicated that the 19 kDa protein, not the 35 kDa protein, is capable of catalyzing the luminescent oxidation of coelenterazine. The primary sequence of the 35 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
110
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 31 publications
0
110
0
2
Order By: Relevance
“…Naturally occurring secreted luciferases are very suitable for this purpose, and this idea stimulates investigation of new bioluminescent systems. To date the cDNAs encoding several secreted luciferases have been cloned (23,24). Vargula luciferase has been expressed in mammalian cells and has shown promising properties as a reporter enzyme (25)(26)(27)(28).…”
Section: Monitoring Of Activity Of A2a and Npy2 G-protein-coupled Recmentioning
confidence: 99%
See 2 more Smart Citations
“…Naturally occurring secreted luciferases are very suitable for this purpose, and this idea stimulates investigation of new bioluminescent systems. To date the cDNAs encoding several secreted luciferases have been cloned (23,24). Vargula luciferase has been expressed in mammalian cells and has shown promising properties as a reporter enzyme (25)(26)(27)(28).…”
Section: Monitoring Of Activity Of A2a and Npy2 G-protein-coupled Recmentioning
confidence: 99%
“…However, its large size (62.2 kDa) probably limits the value of Vargula luciferase as a reporter. Another secreted luciferase tested as a reporter is from the deep sea shrimp O. gracilorostris (24). This luciferase is a complex composed of 35-and 19-kDa proteins, and only the smaller one catalyzes the luminescent oxidation of coelenterazine.…”
Section: Monitoring Of Activity Of A2a and Npy2 G-protein-coupled Recmentioning
confidence: 99%
See 1 more Smart Citation
“…Some squid, when attacked, give off a luminescent secretion which confuses the attacker, and luminescent secretion from a shrimp (Inouye et al 2000 ) may serve a similar purpose. A kind of marine annelid called a scale worm is covered on the dorsal side by scales which fi rst emit fl ashes when the animal is attacked and then are shed, still glowing (Herrera et al 1974 ).…”
Section: Protection From Predationmentioning
confidence: 99%
“…Oplophorus luciferase of the deep sea shrimp Oplophorus gracilorostris is a secretory protein [1] that catalyzes the oxidation of coelenterazine (a luciferin) to emit light (k max = $460 nm) [2]. The luciferase consists of the 19 kDa and 35 kDa proteins with a total molecular weight of 106 kDa [2], and the cDNA cloning of the 19 kDa and 35 kDa proteins showed that both proteins have a putative secretory signal peptide at the amino terminus [2].…”
Section: Introductionmentioning
confidence: 99%